2005
DOI: 10.1097/01.pas.0000157941.88161.39
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratins in Papillary Lesions of the Breast

Abstract: We studied 50 papillary lesions (25 papillomas and 25 papillary ductal carcinomas in situ, DCIS) diagnosed at Singapore General Hospital, for immunohistochemical expression of cytokeratin (CK) 5/6, CK14, and 34betaE12. The immunoscore (proportion of stained cells multiplied by staining intensity) was compared between the two groups. Cytokeratin expression was corroborated by confocal microscopy. Results were applied to a separate series of 43 papillary tumors from Hong Kong (HK). CK5/CK6, CK14, and 34betaE12 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Areas of usual ductal hyperplasia in a papilloma are typically characterized by strong staining of the majority of the epithelial cells in a mosaic pattern, while in contrast, malignant papillary proliferations demonstrate diminished to absent expression of high molecular weight keratins by immunohistochemical methods. [14, 2123] It has recently been suggested that evaluation of estrogen receptor (ER) expression may be a useful adjunct to high molecular weight keratin staining, as well. In one study, a series of 82 core biopsies from papillary lesions were subjected to immunohistochemical analysis.…”
Section: Diagnosismentioning
confidence: 99%
“…Areas of usual ductal hyperplasia in a papilloma are typically characterized by strong staining of the majority of the epithelial cells in a mosaic pattern, while in contrast, malignant papillary proliferations demonstrate diminished to absent expression of high molecular weight keratins by immunohistochemical methods. [14, 2123] It has recently been suggested that evaluation of estrogen receptor (ER) expression may be a useful adjunct to high molecular weight keratin staining, as well. In one study, a series of 82 core biopsies from papillary lesions were subjected to immunohistochemical analysis.…”
Section: Diagnosismentioning
confidence: 99%
“…Böecker and colleagues 18 , 19 reported that a progenitor cell marker stains weakly positive around tumor cells in DCIS but stains diffusely positive in usual ductal hyperplasia. Antibodies to CK5, 7 , 18 CK5/6, 6 , 14 , 20 22 CK14, 6 , 20 , 22 and CK34betaE12 6 , 14 , 21 23 recognize these progenitor cell markers. CK5/6, CK14, and CK34betaE12 stain proliferative cells diffusely (mosaic pattern) in ductal hyperplasia and duct papillomatosis.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 24 , 25 CK14 has been reported to stain positively >95% of cells in tissue from IPUDH patients. 21 , 26 Several studies have reported that CK34betaE12 stains positively 0%–20% of tumor cells in tissue from DCIS patients. 24 , 25 , 27 However, another study reported that 40%–100% of tumor cells stain positively for CK34betaE12 in 10% of patients with DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Benign papillary lesions show heterogeneous staining for ER, positive staining for myoepithelial cells and the hyperplastic epithelial cells express high molecular weight cytokeratins, whereas malignant lesions show homogeneous staining for ER, negative staining for myoepithelial cells and the hyperplastic epithelial cells are negative for high molecular weight cytokeratins. This approach had been found to be useful [58][59][60], even though false positive and false negative cases cannot be totally eliminated [56]. Thus, when dealing with a papillary lesion, both FNAC and NBC do face the same type of challenges [61], despite to a greater extent in the former, and surgical excision for full evaluation is still the optimal approach.…”
Section: Papillary Lesions-accuracy Of Both Fnac and Cnbmentioning
confidence: 95%